Phase transformation, optical and emission performance of zinc silicate glass-ceramics phosphor derived from the ZnO–B2O3–SLS glass system - Mohd Shofri, Muhammad Faris Syazwan; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Fen, Yap Wing; Yaakob, Yazid; Jaafar, Suhail Huzaifa; Wahab, Siti Aisyah Abdul (Multidisciplinary Digital Publishing Institute, 2020)
A new transparent zinc silicate glass-ceramic was derived from the 55ZnO–5B2O3–40SLS glass system via a controlled heat-treatment method. The precursor glass sample was placed through the heat-treatment process at different temperatures to study the progress in phase transformation, optical performance and emission intensity of the zinc silicate glass-ceramics. For this project, material characterization was measured through several tests using densimeter and linear shrinkage measurement, X-ray diffraction (XRD), Fourier transform infrared reflection (FTIR), ultraviolet–visible (UV–Vis) and photoluminescence (PL) spectroscopy. The density and linear shrinkage measurements show that the density of the particular glass-ceramic samples increases with the progression of heating temperature. The XRD analysis displays the result in which the zinc silicate crystal starts to grow after the sample was treated at 700 °C. In addition, the FTIR spectra indicated that the crystallization of the zinc silicate phase occurred with the appearance of SiO4, ZnO4 and Si-O-Zn bands. UV–visible exhibited the small changes when the value for the optical band gap decreased from 3.867 to 3.423 eV, influenced by the temperature applied to the sample. Furthermore, the PL spectroscopy showed an enhancement of broad green emission at 534 nm upon the increased heat-treatment temperature. Thus, it can be concluded there is the progression of crystal growth as the heat-treatment temperature increased; three emission peaks appeared at 529, 570 and 682 nm for the green, yellow and red emissions, respectively.